Motivations for a Career in Dentistry among Dental Students and Dental Interns in Kenya - Ochiba M. Lukandu; Lilian C. Koskei; Elizabeth O. Dimba (International Journal of Dentistry)
A number of factors have been cited as determinants for choosing a career in dentistry around the globe. The purpose of this study was to determine motivations for a career in dentistry among dental students and dental interns in Kenya. This was a cross-sectional study where 293 individuals participated by filling and returning self-administered questionnaires. The mean age of all respondents was 22.3 years. Overall, 59.5% of the respondents had selected dentistry as their preferred career at the end of high school. Majority (76.1%) of the respondents agreed that personal interest in dentistry was an important motivating factor for them. This was followed closely by a desire to help or serve people (74%), a desire for a flexible work schedule (63%), and an aspiration to be self-employed (61.8%). There was no difference between males and females regarding these as motivating factors. On the other hand, among factors that the respondents felt had the lowest influence on their choice of dentistry was parental influence, where only 22% of the respondents indicated that this was a motivating factor for them. Other potential motivating factors such as influence by friends and siblings (30.3%) as well as career talk and guidance (41.3%) were also ranked low. In general, the respondents indicated that they were motivated much more by personal and humanitarian factors, when compared to financial and societal factors.